Conectividade funcional potencial em paisagens antropizadas: estrutura de resistência de caminhos de menor custo no retorno de Melipona quadrifasciata - Furlan, Letícia Oliveira (Universidade Federal de São Carlos, 2026)
Habitat fragmentation and the expansion of anthropogenic areas can compromise pollinator functional connectivity by altering landscape permeability and hindering their movement and survival. In this context, this study evaluated the functional connectivity of the native stingless bee Melipona quadrifasciata, commonly known as “mandaçaia”, in an anthropized landscape, investigating the influence of distance, seasonality, and the characteristics of potential corridors on bee return success and return speed. Release experiments were conducted during the four seasons of the year at five distances ranging from 500 to 2,500 m from the colony and were integrated with ecological corridor modeling based on least-cost paths generated from resistance surfaces built using land-use and land-cover data and the Normalized Difference Vegetation Index (NDVI). A total of 240 releases were performed, 60 in each season, of which 155 resulted in successful returns to the colony (64.6%). Return probability decreased significantly with increasing distance, ranging from approximately 79% at 500 m to 46% at 2,500 m, highlighting distance as the main limiting factor for movement. Seasonal differences were also observed, with lower return rates and slower return speeds in autumn and better performance during spring and summer. Potential corridors showed high spatial stability across seasons, with similarity indices exceeding 0.91 and maximum recurrence covering 87.36% of the total corridor area. However, the functionality of these corridors varied over time. Distance was the main factor associated with the probability of return, whereas landscape heterogeneity influenced the speed at which bees returned to the colony. The results indicate that the functional connectivity of M. quadrifasciata depends primarily on displacement distance but is also influenced by matrix functional quality and landscape heterogeneity. These findings reinforce the importance of simultaneously considering species movement capacity and matrix permeability in conservation strategies and landscape planning.
Potential functional connectivity in anthropized landscapes: resistance structure of least-cost paths for the return of Melipona quadrifasciata
Keywords: Conectividade funcional; Ecologia da paisagem; Abelhas sem ferrão; Melipona quadrifasciata; Caminhos de menor custo; Polinizadores; Functional connectivity; Landscape ecology; Stingless bees; Least-cost paths; Pollinators; CIENCIAS BIOLOGICAS::ECOLOGIA; 15. Vida Terrestre